Bee pollination in the shadows: The role of pseudopollen and agamospermy in the mycoheterotrophic orchid Gastrodia elata - Kenji Suetsugu; Takenori Yamamoto (Plants, People, Planet, 2024)
Societal Impact Statement The family Orchidaceae is renowned for its reliance on specialized pollinators and mycorrhizal symbioses. This study examined how the nonphotosynthetic orchid Gastrodia elata thrives on the dim forest floor, focusing on its pollination biology, particularly the chemical properties of pseudopollen and reproductive assurance mechanisms. It was found that G. elata mainly relies on Lasioglossum bees, attracted by its starch‐rich pseudopollen. Additionally, G. elata in the studied population can produce fruit through agamospermy (seeds from unfertilized ovules). Overall, the findings reveal that G. elata relies on fungi for nutrition and employs reproductive strategies such as mimicking pollen to attract bees and resorting to asexual reproduction when pollinators are scarce. Summary Mycoheterotrophy is an adaptation that allows survival in environments with low irradiance and minimal competition from autotrophic plants. However, such environments can negatively impact bee pollination, as most bees prefer open habitats. Despite this, the mycoheterotrophic orchid Gastrodia elata is known to rely on Lasioglossum bees for pollination. We investigated the reproductive biology of G. elata to understand how it overcomes pollinator limitation. Our research focused on the chemical composition and anatomical basis of G. elata pseudopollen (a substance that mimics pollen and may facilitate pollination), based on micromorphological and nutritional analyses, as well as observations of pollinator behavior. Additionally, we explored the potential presence of autogamy or agamospermy as mechanisms for reproductive assurance. The pseudopollen in G. elata originates from the disintegration of the adaxial parenchymatous tissue of the callus and is rich in starch. This contrasts with pseudopollen in most orchids, which typically originates from lip hairs and whose potential attractant is protein. Lasioglossum bees pollinating G. elata visit multiple flowers and actively collect pseudopollen. Furthermore, agamospermy serves as a reproductive safeguard in shaded habitats where insect‐mediated pollination is infrequent, at least in the investigated population. Our findings suggest that Gastrodia elata pseudopollen plays an important role in enhancing insect‐mediated pollination, particularly in relatively open habitats, while agamospermy ensures fruit set in shaded environments of the investigated population. Both pseudopollen production and agamospermy likely help overcome the pollination constraints posed by the mycoheterotrophic lifestyle.